Suffer the children - Adam Creed (Faber, 2009)
London. A paedophile is brutally murdered in his own home, and to protect other known offenders the police must interview the families of their victims. Everywhere DI Will Wagstaffe (Staffe) turns the boundaries between right and wrong have been blurred but the main question remains: just how far would you go to protect your children?